The Influence of Digital Education Factors and Online Business Innovation on the Economic Independence of People in Yogyakarta Region - Judijanto, Loso; Imanirubiarko, Sabda (Westscience Press, 2023)
This research investigates the influence of digital education factors and online business innovation on community economic independence in the Special Region of Yogyakarta. A quantitative analysis was conducted using a sample of 193 participants, exploring the relationships between digital education, online business innovation, and economic independence. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling with Partial Least Squares (SEM-PLS) were employed to analyze the data. The results revealed significant and positive relationships between digital education factors and both online business innovation and economic independence. Online business innovation was also found to positively influence economic independence. The study provides valuable insights for policymakers, educators, and community stakeholders, emphasizing the importance of investing in digital education initiatives and fostering innovative online business practices to enhance community economic independence.